RETRACTED: Waste-to-Renewable Energy Transition: Biogas Generation for Sustainable Development - Atchike, Desire Wade; Irfan, Muhammad; Ahmad, Munir; Rehman, Mubeen Abdur (Frontiers in Environmental Science, 2022)
To attain renewable energy goals, many developing countries, including Malaysia, acknowledge the adoption of waste-to-renewable energy (WTRE) technologies being the best means. The conversion of animal dung into biogas is one of the similar techniques. For a considerable amount of time, Malaysia has witnessed an increase in animal husbandry to generate massive feedstock, which can serve as the raw material for the generation of biogas. With the implementation of WTRE technologies, Malaysia is starting to use a suitable method of power generation from the conversion of animal dung to biogas. The application of an alternative method of power generation by Malaysia is converting animal dung to biogas. Uses of animal dung conversion to biogas is considered as a suitable method for power generation. For the application of WTRE technologies, this phenomenon is examined by the current article. As a further step, a thorough analysis of Malaysia's waste management issues and the energy mix have been done. The current issue at hand regarding the power generation in Malaysia is optimizing new and suitable energy sources. In this regard, WTRE transition has been identified as the primary and inevitable source of the energy transition. The article consists of an explanation of various technologies of power generation utilizing municipal waste. Malaysia's massive potential capacity to produce biogas energy through waste has been analytically identified. Malaysian animal dung can yield biogas up to 1317.20 mm3/annum, which can eventually result in power generation of 2.1× 104 KWH/annum. Relevant policies are discussed for Malaysia to implement long-term biogas generation. This study did not include the obstacles to WTRE in Malaysia and other developing countries, providing an opportunity for future works to consider this research dimension.